THE EFFECT OF TRICOMPONENT ATTITUDE MODEL AND INTEGRATED MARKETING COMMUNICATION ON THE PURCHASE DECISION OF ASUS LAPTOP WITH BRAND IMAGE AS INTERVENING VARIABLE - Aris Kurniawan (SEAN Institute, 2022)
This study examines and analyzes the effect of the tricomponent attitude model and integrated marketing communication on purchasing decisions for Asus laptops, with a brand image as an intervening variable. The study was conducted on Asus laptop users in Jakarta and surrounding areas using a Likert scale questionnaire, determining the sample using purposive sampling and obtaining 85 respondents. The collected data is processed using the SmartPLS version 3.0 application. The results show that based on the research, the Tricomponent Attitude Model does not significantly affect Brand Image, Integrated Marketing Communication significantly affects Brand Image, Tricomponent Attitude Model significantly affects Buying Decision, Integrated Marketing Communication significantly affects Buying Decision, Brand Image significantly affects Buying Decision, Brand Image has no effect as the intervening variable in the relationship or influence of the Tricomponent Attitude Model on the Purchase Decision, Brand Image has an effect as the intervening variable in the relationship or the result of Integrated Marketing Communication on the Purchase Decision